THE USE OF ANGIOTENSIN CONVERTING ENZYME INHIBITORS AFTER MYOCARDIAL INFARCTION. WHAT DO EVIDENCE-BASED MEDICINE DATA SPEAK FOR? - S. Yu. Martsevich (Рациональная фармакотерапия в кардиологии)
The main trails proven angiotensin converting enzyme (ACE) inhibitor effects on the life prognosis after myocardial infarction (MI) are described. Different tactics of ACE inhibitors therapy in post MI patients are presented. Approaches to the choice of a specific ACE inhibitor are discussed.